Morton Neuroma Excision: What Are We Really Doing? Which Retractor is Superior?. Issue 3 (14th September 2018) - Shah, Ashish; Pinter, Zachariah; Lehtonen, Eva; Naranje, Sameer; Odom, Christopher; Paul, Kyle; Huntley, Samuel; Dahlgren, Nicholas; DeBell, Henry
Category: Midfoot/Forefoot Introduction/Purpose: Morton's Neuroma is a benign enlargement of the second or third common digital branch of the medial plantar nerve. This causes a compressive neuropathy of the distal medial plantar nerve. When conservative management fails, surgery becomes the treatment of choice via either a dorsal or plantar approach to the nerve. When using a dorsal approach for a Morton Neurectomy, neuroma commonly recurs due to insufficiently resection of the medial plantar nerve. It is unclear how far the nerve can be resected and which type of retractor provides superior visualization to allow greater resection. The present cadaveric study investigates how proximally the nerve can be resected and examines both the Laminar spreader and Galpie retractor to determine which instrument facilitates maximal proximal resection of the nerve. Methods: This study involved 12 fresh-frozen below-knee cadaver specimens that underwent a dorsal approach to the medial plantar nerve with proximal resection of the nerve in both the 2nd and 3rd intermetatarsal spaces as is performed during a Morton Neurectomy. The senior surgeon made a 3 cm incision just proximal to the 2nd and 3rd webspaces, and used blunt dissection to the level of the transverse intermetatarsal ligament. The transverse intermetatarsal ligament was then transected, and either a Laminar spreader or Galpie retractor was used to improve visualization of the intermetatarsal space. The medial plantar nerve was then identified and transected, and the lengths of the distal segment of the cut nerves were measured and recorded. These values were then compared based on the retractor employed. Results: In the 2nd intermetatarsal space, the Laminar spreader allowed the nerve to be dissected an average of 2.42 cm proximal to the distal end of the 3rd metatarsal (head)compared to 1.93 cm by the Galpie retractor. Thus, use of the Laminar spreader rather than the Galpie retractor resulted in greater resection of the nerve, although this was not significant. In the 3rd intermetatarsal space, the Laminar spreader allowed the nerve to be dissected an average of 2.14 cm proximal to the distal end of the 3rd metatarsal, while the Galpie retractor allowed 1.48 cm. Thus, use of the Laminar spreader in the 3rd intermetatarsal space resulted in greater excision of the nerve than the Galpie retractor, although this was not significant. Conclusion: These results demonstrate that use of the Laminar spreader during dorsal approach to a Morton Neuroma results in superior proximal resection of the medial plantar nerve when compared to use of the Galpie retractor, thereby decreasing the risk of recurrent Morton Neuroma. Further evaluation of the available retractors is needed to support the superiority of the laminar spreader compared to the Galpie retractor.